Comparative efficacy and acceptability of cognitive behavioral therapy delivery formats for insomnia in adults: A systematic review and network meta-analysis. (August 2022) - Gao, Ya; Ge, Long; Liu, Ming; Niu, Mingming; Chen, Yamin; Sun, Yue; Chen, Ji; Yao, Liang; Wang, Qi; Li, Zhifan; Xu, Jianguo; Li, Muyang; et al.
Summary: This review compared the efficacy and acceptability of different delivery formats for cognitive behavioral therapy for insomnia (CBT-I) in insomnia. We searched five databases for randomized clinical trials that compared one CBT-I delivery format against another format or control conditions for insomnia in adults. We used pairwise meta-analyses and frequentist network meta-analyses with the random-effects model to synthesize data. A total of 61 unique trials including 11, 571 participants compared six CBT-I delivery formats with four control conditions. At post-intervention, with low to high certainty evidence, individual, group, guided self-help, digital assisted, and unguided self-help CBT-I could significantly increase sleep efficiency and total sleep time (TST) and reduce sleep onset latency (SOL), wake after sleep onset (WASO), and insomnia severity compared with treatment as usual (MD range for sleep efficiency: 7.81%–12.45%; MD range for TST: 16.14–33.96 min; MD range for SOL: −22.42 to −13.81 min; MD range for WASO: −40.84 to −19.48 min; MD range for insomnia severity: −6.40 to −3.93) and waitlist (MD range for sleep efficiency: 7.68%–12.32%; MD range for TST: 12.67–30.49 min; MD range for SOL: −19.07 to −10.46 min; MD range for WASO: −47.10 to −19.15 min; MD range for insomnia severity: −7.59 to −5.07). The effects of different CBT-I formats persisted at short-term follow-up (4 wk–6 mo). Individual, group, and digital assisted CBT-I delivery formats would be the more appropriate choices for insomnia in adults, based on post-intervention and short-term effects. Further trials are needed to investigate the long-term effects of different CBT-I formats.